2015
DOI: 10.3892/ijo.2015.3206
|View full text |Cite
|
Sign up to set email alerts
|

Sedanolide induces autophagy through the PI3K, p53 and NF-κB signaling pathways in human liver cancer cells

Abstract: Abstract. Sedanolide (SN), a phthalide-like compound from celery seed oil, possesses antioxidant effects. However, the effect of SN on cell death in human liver cancer cells has yet to be determined. In this study, cell viability determination, monodansylcadaverine (MDC) fluorescent staining and immunoblot analysis were performed to determine autophagy induction and autophagy-induced protein expression changes via molecular examination after human liver cancer (J5) cells were treated with SN. Our studies demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…According to the literature, celery seed contains approximately 2% of volatile oil [9]. Previous literature studies do not show this method of treatment in the case of hydrodistillation of essential oil from celery seeds.…”
Section: Efficiency Of Ultrasonic Hydrodistillationmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the literature, celery seed contains approximately 2% of volatile oil [9]. Previous literature studies do not show this method of treatment in the case of hydrodistillation of essential oil from celery seeds.…”
Section: Efficiency Of Ultrasonic Hydrodistillationmentioning
confidence: 98%
“…The volatile constituents having a phthalide skeleton: sedanenolide, 3-butylphthalide, sedanolide, and Z-ligustilide are responsible for the celery-like aroma of the essential oil and the whole plant [6,9]. The first two of these were identified in the essential oil from sonicated celery seeds.…”
Section: Aroma Profilementioning
confidence: 99%
“…Additionally, Cui et al reported that p53/DRAM-mediated autophagy contributes to radiation-induced death in MCF-7 breast cancer cells [38]. Hsieh et al reported that sedanolide promotes autophagy via the p53/DRAM signaling pathway in human liver cancer J5 cells [39]. Wei et al also demonstrated that XingNaoJing inhibits autophagy by suppressing the p53/ DRAM signaling pathway in PC12 cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…RelA(p65), a member of the NF-κB family, can target several sites in the promoter of the BECN1 ( Beclin 1 ) gene, modulating the level of autophagy in various human cell lines [ 58 , 59 ]. In turn, other members of the NF-κB family can be activated by DNA damage with the involvement of autophagy, as reported for many cell lines and several signaling proteins [ 60 , 61 , 62 , 63 , 64 , 65 ]. Bcl-2/E1B-19K interacting protein 3 (BNIP3) is a mitochondrial protein cooperating with several anti-apoptotic proteins and inducing cell death with the involvement of autophagy [ 66 , 67 ].…”
Section: Nf-κb Signaling Pathways and Autophagymentioning
confidence: 91%